Analisis Misi Kontekstual Berbasis Entrepreneurship Dan Dampaknya Terhadap Pertumbuhan Gereja - Afandi, Yuliana T.W. Ayu; Laukapitang, Yunus D.A.; Panggarra, Robi; Wijaya, Hengki (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
This study examines entrepreneurship-based contextual mission services and their impact on church growth in Liwa, West Lampung. Data were obtained through direct observation to see field conditions, interviews with mission actors using a qualitative Live History approach, and follow-up interviews with secondary sources through snowball sampling. In addition, literature studies are carried out by studying books and journals as the basis of theory. The results of the study show that contextual missions based on entrepreneurship are a means of preaching the gospel by utilizing entrepreneurial activities as a bridge so that the gospel is more relevant and touches aspects of community welfare. This mission model has an impact on the growth of the church both quantitatively and qualitatively. Quantitatively, the number of congregations increased; Qualitatively, the congregation is increasingly active in church service through offerings, discipleship, social services, participation in church activities, and involvement in the management of BPJ.